Organizações sociais de saúde: potencialidades e limites na gestão pública - Rodrigues, Clarita Terra [UNESP]; Spagnuolo, Regina Stella [UNESP] (Universidade Federal de Goias, 2014)
The present study had the aim to become familiar with the Social Organization of Health (OSS, as per its acronym in Portuguese) from a municipality of the state of São Paulo from the managers’ viewpoint. It is a qualitative singlesubject study, with seven participants from the Council of Healers. Data were collected through a non-directive interview, resulting in four thematic categories: 1. The historical process, social transformations and the local OSS. 2. The OSS management contract: agility and new learning. 3. OSS: A new management possibility. 4. Limits of local OSS management and its control mechanisms. The study shed light on the OSS’s management potentials, with emphasis on the service’s agility and the objectivity of the management contract. As limitations, we point out its control mechanisms and the very low level of social participation.

Se objetivó conocer el gerenciamiento de una Organización Social de Salud (OSS) de un municipio del interior paulista en la perspectiva de los administradores. Estudio cualitativo, tipo Estudio de Caso Único, con siete participantes del Consejo de Curadores. Datos recolectados mediante entrevista no directiva entre marzo y mayo de 2012, analizados según análisis de contenido, resultando en cuatro categorías temáticas: 1. El proceso histórico, las transformaciones sociales y la OSS local. 2. El contrato de gestión de la OSS: agilidad y nuevos aprendizajes. 3. OSS: una nueva posibilidad de gestión. 4. Limitaciones en el gerenciamiento y mecanismos de control de la OSS local. El estudio hizo visibles las potencialidades del gerenciamiento de la OSS, habiéndose destacado la agilidad de los servicios y la objetividad del contrato de gestión. Se presentaron como limitaciones la escasa participación social y sus mecanismos de control.

Este estudo objetivou conhecer o gerenciamento de uma Organização Social de Saúde (OSS) de um município do interior paulista, na perspectiva dos gestores. Trata-se de estudo qualitativo do tipo Estudo de Caso Único, com sete participantes do Conselho de Curadores. Os dados foram coletados por meio de entrevista não diretiva, entre os meses de março e maio de 2012, e analisados segundo análise de conteúdo, resultando em quatro categorias temáticas: 1. O processo histórico, as transformações sociais e a OSS local; 2. O contrato de gestão da OSS: agilidade e novos aprendizados; 3. OSS: uma nova possibilidade de gestão; 4. Limitações no gerenciamento e nos mecanismos de controle da OSS local. O estudo deu visibilidade às potencialidades do gerenciamento da OSS, sendo destaques a agilidade dos serviços e a objetividade do contrato de gestão. Apresentaram-se como limitações a escassa participação social e seus mecanismos de controle.
Social organizations of health: potentials and limits of public management
Organizaciones sociales de salud: potencialidades y límites en la gestión pública
Keywords: Social organization; Health management; Models; Organizational; Organización social; Gestión en salud; Modelos organizacionales; Organização social; Gestão em saúde; Modelos organizacionais